The potential use of chitosan as a biopolymer additive for enhanced mechanical properties and water resistance of earthen construction - Aguilar R. (2016)
The study investigates the feasibility of using chitosan biopolymer as an admixture, or as an external coating, for earthen constructions to improve their resistance in two components: water induced degradation and key mechanical properties. The resistance to water induced degradation was evaluated in terms of contact angle and drip erosion tests, while the influence on mechanical properties was measured through compressive, tensile and three-point bending tests. The results indicate that the use of low concentrations of chitosan can improve significantly the performance in the two components and therefore was found to be a promising treatment for new or existing construction.